Management Practices of Head and Neck Cancer in Chinese Tertiary Care Hospitals: A Multicenter Questionnaire-Based Survey Among Oncologists. (26th February 2020) - Anwei, Zhao; Xin, Sun; Fei, Tang Qiao; Ziyu, Jin; Liu, Fa-Yu
This survey was conducted to determine the head and neck cancer (HNC) treatment strategies followed by oncologists in Chinese hospitals. It was a questionnaire-based survey, conducted from October 2017 to January 2018 in 100 random tertiary hospitals in 21 cities of China to elicit information from oncologists on the management practices for treating HNC in China. A validated, structured questionnaire was used for formal investigation with oncologists. The questions regarding HNC types, treatment strategies used for locally advanced head and neck cancer (LA HNC) and recurrent/metastatic head and neck cancer (r/m HNC), diagnosis and prognostic factors were included. The results were presented as percentages. Among the 272 oncologists, 93.4% were from tertiary care hospitals, with 35.3% and 36.4% patients from radiotherapy (RT) and oncology department, respectively. Nasopharyngeal carcinoma was the most commonly treated type of HNC according to 65.1% oncologists. Patients aged >75 years have worse prognosis and 65% oncologists corroborated that age of the patients influences treatment decision. Most of the oncologists (77.6%) preferred chemotherapy (CT) + anti–epidermal growth factor receptor targeted therapy as the first-line therapy for r/m HNC. Approximately 95% of oncologists considered induction chemotherapy (ICT) to retain organ functions and tumor shrinkage and 43.4% preferred ICT followed by chemoradiotherapy or ICT combined with RT followed by targeted therapy for LA HNC. For the management of HNC, Chinese oncologists recommended ICT with RT and targeted therapy for LA HNC and CT regimen combined with targeted therapy for r/m HNC.